2021
DOI: 10.4018/978-1-7998-8327-2.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Workplace

Abstract: The hybrid workplace is a concept on the lips of every industry trend in the world today. With digitalization becoming more normalized across every sphere in the global village. Every workplace needs to maximize and transcend obstacles and innovations to ease into the hybrid workplace. The COVID-19 pandemic brought a wave for an increased need for a hybrid workplace. Although some countries have relaxed the lockdown in their states, businesses are taking their time to set up a more formidable work arrangement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Reduce information asymmetry in the stock market have negative effects while enhancing market information value will lead to improve the efficiency of financial resources. In accordance with research by Iqbal et al (2021) and Zhang et al (2021). ESG disclosure decreases the cost of corporate debt financing and increases the financial flexibility of the firm.…”
Section: Cefsupporting
confidence: 82%
See 1 more Smart Citation
“…Reduce information asymmetry in the stock market have negative effects while enhancing market information value will lead to improve the efficiency of financial resources. In accordance with research by Iqbal et al (2021) and Zhang et al (2021). ESG disclosure decreases the cost of corporate debt financing and increases the financial flexibility of the firm.…”
Section: Cefsupporting
confidence: 82%
“…ESG disclosure decreases the cost of corporate debt financing and increases the financial flexibility of the firm. In addition to the previous findings, (Iqbal et al, 2021), and (Zhang et al, 2021), have found that ESG performance has positive effects on corporate finance efficiency as well as on other factors. All of the overall digital finance indices, as well as the digitalization level, coverage width, and usage depth of digital finance are found to be positively linked with corporate financing efficiency at the one percent level of significance (Yao et al, 2021).…”
Section: Cefsupporting
confidence: 46%
“…Traditionally, the idea of “workplace” has been associated with a specific location. A hybrid workplace refers to working arrangements combining traditional on-site office settings and remote working (Iqbal, Khalid, & Barykin, 2021). While there are myriad ways to conceptualize a hybrid workplace model, the current study follows Radonić, Vukmirović, and Milosavljević (2021) approach by conceptualizing it as both the adoption and/or availability of “telework” and “flexible work”.…”
Section: Research Context and Backgroundmentioning
confidence: 99%
“…The hybrid mode of work is here to stay since organizations recognize the advantages that come with it, such as reduced expenses, maximized productivity and technological advancement (Alexander et al, 2021; Iqbal, Khalid, & Barykin, 2021). In fact, the hybrid mode of work is increasingly being recognized as the future of work (Dowling, Goldstein, Par, & Price, 2022).…”
Section: Introductionmentioning
confidence: 99%